Sociality and a proposed analytic1 for investigating communal being‐ness. Issue 4 (November 2016) - Studdert, David
Abstract: This paper thinks about ourselves as communal beings, tied together and created by common actions of sociality. The perspective presented here stems from what Wills (this issue) terms the Aristotelian position that community is always with us, but it tries to move beyond that simple statement, to ask questions, and propose answers to the question of how: how is community always with us? Embedded in that question of course are others: what are the implications of such an investigation for a discipline tasked to investigate the social? How do we investigate the social of which we are both observer and act‐or? What does thinking differently about community mean? What would such a different approach to community look like and finally, how does community work? To confront these questions the paper proposes an investigative analytic which positions communal being‐ness as the source of ontological meaning. It proposes that the 'who' we are, our being‐ness/identity, is the outcome of constant sociality enacted in common and created and sustained in common through the inter‐relational linking of action, materiality, subjectivity, speech and the world of accepted meanings. It proposes a social science means for the investigation of this sociality, this communal being‐ness of ours : that is a method for studying the social not built upon concepts borrowed from other fields, but particular to the task at hand. It argues that Hannah Arendt's (1958) account of the creation of our human being‐ness as a temporary outcome held in common, provides the foundation for thinking inter‐relationally about our communing, and about the social world, to which that thinking must be inexorably bound.